Development of the fast, simple and fully validated high performance liquid chromatographic method with diode array detector for quantification of testosterone esters in an oil-based injectable dosage form - Kozlik, Petr; Tircova, Barbora (Steroids, 2016)
Counterfeit steroids are available on the black market, ultimately to consumers who believe they are buying a legitimate pharmaceutical item from the labeled company. In many cases, counterfeit steroids can contain lower doses or some products can be overdosed. This can unwittingly expose users to a significant health risks. The mixture of testosterone propionate, phenylpropionate, isocaproate and decanoate in an oil-based injectable dosage form belongs to the one of the most misused illicit drugs by a variety of athletes. This study developed a new, fast, simple and reliable HPLC method combined with a simple sample preparation step to determine testosterone propionate, phenylpropionate, isocaproate and decanoate in an oil-based injectable dosage form without the use of sophisticated and expensive instrumentation. The developed analytical procedure provides high throughput of samples where LC analysis takes only 6min and sample preparation of oil matrix in one step takes approximately 10min with precision ranging from 1.03 to 3.38% (RSD), and accuracy (relative error %) within ±2.01%. This method was found to be precise, linear, accurate, sensitive, selective and robust for routine application in screening of commercial pharmaceutical products based on content of mentioned testosterone esters in their oil-based injectable dosage form for counterfeit drugs. This method was successfully applied to the analysis of nine samples of commercial testosterone mixtures purchased from various sources and will be further used as an effective screening method for determination of previously mentioned testosterone esters in samples confiscated by Institute of Forensic Science (Slovakia) during the illegal trade.
Keywords: Chromatography, High Pressure Liquid; Humans; Temperature; Substance Abuse Detection; teplota; padělané léky; Testosterone Congeners; Oil-based injectables; lidé; Testosterone esters; High performance liquid chromatography; Anabolic steroids; reprodukovatelnost výsledků; Testosterone; Reproducibility of Results; kongenery testosteronu; Counterfeit Drugs; odhalování abúzu drog; testosteron; Counterfeit drugs; vysokoúčinná kapalinová chromatografie